PERANCANGAN SISTEM INFORMASI PENJUALAN BERBASIS WEB PADA UKM ECOVILLAGE SILIMALOMBU - Dina Ismayanti, (2022)
In this era of digitalization, all types of business sectors can publish all types of businesses using only gadgets and the internet. Information technology can encourage a small organization in maximizing its business, such as the type of business of selling a product produced by the organization. Ecovillage Silimalombu is one of the micro, small and medium enterprises engaged in the tourism sector and the sale of local products. By utilizing technological developments, a Web-Based Exploration Information System Design was made at ukm Ecovillage Silimalombu with the hope of changing manual transactions to modern web-based to facilitate sales, and can become a medium for disseminating information about products on Ukm Ecovillage. This research uses the waterfall method with a needs analysis method, namely PIECES as problem identification. The results of this study are in the form of web applications that can already be used by users.